Transcriptome analysis reveals that jasmonic acid biosynthesis and signaling is associated with the biosynthesis of asperosaponin VI in Dipsacus asperoides - Xu, Jiao; Hu, Zhengping; He, Hua; Ou, Xiaohong; Yang, Yang; Xiao, Chenghong; Yang, Changgui; Li, Liangyuan; Jiang, Weike; Zhou, Tao (Frontiers in Plant Science, 2022)
Dipsacus asperoides is a perennial herb, the roots of which are abundant in asperosaponin VI, which has important medicinal value. However, the molecular mechanism underlying the biosynthesis of asperosaponin VI in D. asperoides remains unclear. In present study, a comprehensive investigation of asperosaponin VI biosynthesis was conducted. The content of asperosaponin VI was significantly accumulated in two-leaf stage roots, and the spatial distribution of asperosaponin VI was localized in the xylem. The concentration of asperosaponin VI gradually increased in the root with the development process. Transcriptome analysis revealed 3916 unique differentially expressed genes (DEGs) including 146 transcription factors (TFs) during root development in D. asperoides. In addition, α-linolenic acid metabolism, jasmonic acid (JA) biosynthesis, JA signal transduction, sesquiterpenoid and triterpenoid biosynthesis, and terpenoid backbone biosynthesis were prominently enriched. Furthermore, the concentration of JA gradually increased, and genes involved in α-linolenic acid metabolism, JA biosynthesis, and triterpenoid biosynthesis were up-regulated during root development. Moreover, the concentration of asperosaponin VI was increased following methyl jasmonate (MeJA) treatment by activating the expression of genes in the triterpenoid biosynthesis pathway, including acetyl-CoA acetyltransferase (DaAACT), 3-hydroxy-3-methylglutaryl coenzyme A synthase (DaHMGCS), 3-hydroxy-3-methylglutaryl coenzyme-A reductase (DaHMGCR). We speculate that JA biosynthesis and signaling regulates the expression of triterpenoid biosynthetic genes and facilitate the biosynthesis of asperosaponin VI. The results suggest a regulatory network wherein triterpenoids, JA, and TFs co-modulate the biosynthesis of asperosaponin VI in D. asperoides.